2004
DOI: 10.3732/ajb.91.12.2051
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in calyx tube length of Clematis stans (Ranunculaceae): a strategy for pollination by two bumble bee species with different proboscis lengths

Abstract: We examined the adaptive significance of a temporal decrease in the calyx tube length of Clematis stans, a dioecious species pollinated by Bombus diversus (long proboscis) and B. honshuensis (short proboscis). We compared visitation frequency, pollen removal, pollen deposition, and fruit set after a single visit among three flower stages, differentiated by calyx tube length. Bombus diversus frequently visited and removed significantly more pollen from long flowers. Bombus honshuensis visited and tended to remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 40 publications
(57 reference statements)
3
37
0
Order By: Relevance
“…In some species of Clematis , nectar is produced on the ventral side of the lower part of the stamen filaments or lower part of the staminodes (Schaffnit, 1904; Daumann & Slavíková, 1968). For Clematis stans Siebold & Zucc., an origin from the ‘base of the calyx tube’ has been mentioned, but without a precise indication of the site of the secretory tissue (Dohzono & Suzuki, 2002; Dohzono, Suzuki & Murata, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In some species of Clematis , nectar is produced on the ventral side of the lower part of the stamen filaments or lower part of the staminodes (Schaffnit, 1904; Daumann & Slavíková, 1968). For Clematis stans Siebold & Zucc., an origin from the ‘base of the calyx tube’ has been mentioned, but without a precise indication of the site of the secretory tissue (Dohzono & Suzuki, 2002; Dohzono, Suzuki & Murata, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, bumblebees have been reported to visit these flowers (L. album [17] [27]; M. urticifolia [28] [29]). Many studies have shown that in long-tubed flower species, flower dimensions such as corolla length and corolla tube length are correlated with pollinator size [22] [30] [31]. However, nectar robbers sometimes seriously decrease the fitness of long-tubed flower species [32], and adaptive changes in flower traits to prevent nectar robbing have been reported in some plants [9] [11].…”
Section: Introductionmentioning
confidence: 99%
“…Spur or floral tube lengths in many groups of flowering plants are positively correlated with the lengths of the mouthparts (proboscis) of certain pollinators, implying specialized relationships between the species (Grant and Grant 1965, Inouye 1980, Nilsson 1988, Suzuki 1992, Dohzono et al 2004). Such specialist mutualisms may be more vulnerable to invasive alien pollinators than generalist plants that are visited by a variety of native pollinators.…”
Section: Introductionmentioning
confidence: 99%